(untitled) (Texas Journal of Medical Science, 2022)
This article describes the X-ray capabilities in the diagnosis of lumbar stenosis of the spine which is an anatomical and pathological condition involving narrowing of the spinal canal of the lumbar spine or one or more lumbar foraminal openings. The vital method of examination is X-ray which is usually the first step to detect a degenerative process, and in this article the authors try to maximize the capabilities of diagnosis of a degenerative process like lumbar stenosis of the spine.